2020
DOI: 10.3390/molecules25235537
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Separation of Breynia retusa (Dennst.) Alston Bark, Fruit and Leaf Constituents from Bioactive Extracts

Abstract: Breynia retusa (Dennst.) Alston (also known as Cup Saucer plant) is a food plant with wide applications in traditional medicine, particularly in Ayurveda. Extracts obtained with four solvents (dichloromethane, methanol, ethyl acetate and water), from three plant parts, (fruit, leaf and bark) were obtained. Extracts were tested for total phenolic, flavonoid content and antioxidant activities using a battery of assays including 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
(39 reference statements)
2
9
0
Order By: Relevance
“…Moreover, Geranium pyrenaicum ethyl acetate extract was more toxic to cancer cells than Geranium robertianum ethyl acetate extract, and the difference was especially marked in case of HeLa cells, 32.34 vs. 217 µg/mL, respectively. Geranium robertianum aqueous extracts (infusion, decoction) showed variable cytotoxicity against cancer cells (GI 50 45.68-380 µg/mL) [24], whereas, we have observed consistent anticancer activity of Geranium pyrenaicum aqueous extract towards all tested cell lines with high selectivity (Table 5). In another paper based on similar study design, Graça, Dias, Barros, Calhelha, Santos and Ferreira [23] reported the cytotoxicity of Geranium molle L. extracts towards the same cancer panel and PLP2 cells.…”
Section: Cytotoxic Evaluationsupporting
confidence: 52%
See 4 more Smart Citations
“…Moreover, Geranium pyrenaicum ethyl acetate extract was more toxic to cancer cells than Geranium robertianum ethyl acetate extract, and the difference was especially marked in case of HeLa cells, 32.34 vs. 217 µg/mL, respectively. Geranium robertianum aqueous extracts (infusion, decoction) showed variable cytotoxicity against cancer cells (GI 50 45.68-380 µg/mL) [24], whereas, we have observed consistent anticancer activity of Geranium pyrenaicum aqueous extract towards all tested cell lines with high selectivity (Table 5). In another paper based on similar study design, Graça, Dias, Barros, Calhelha, Santos and Ferreira [23] reported the cytotoxicity of Geranium molle L. extracts towards the same cancer panel and PLP2 cells.…”
Section: Cytotoxic Evaluationsupporting
confidence: 52%
“…The acetone extract exerted highest cytotoxicity against all tumor (GI 50 -50% of growth inhibition, 57-71 µg/mL) and non-tumor (GI 50 176 µg/mL) cell lines [24]. Interestingly, cytotoxicity of Geranium robertianum n-hexane extract was noticeably lower towards cancer cells (GI 50 151-179 µg/mL) [24] than we have observed (Table 5) for Geranium pyrenaicum nhexane extract (CC 50 53.72-75.46 µg/mL), in case of HeLa cells, this difference was vs. 73.28 µg/mL, respectively. Moreover, Geranium pyrenaicum ethyl acetate extract was more toxic to cancer cells than Geranium robertianum ethyl acetate extract, and the difference was especially marked in case of HeLa cells, 32.34 vs. 217 µg/mL, respectively.…”
Section: Cytotoxic Evaluationmentioning
confidence: 49%
See 3 more Smart Citations